Design and Construction of Magnetic Support Construction Separator on Track V 33 BC-5 at Greenzone 2 - Fajar Mulyana; Akmal Nafsa Ulya Haqqi; Devi Handaya (Recent in Engineering Science and Technology, 2025)
The process of shredding and sorting waste in the Pre Processing method is one of PT Solusi Bangun Indonesia's contributions in overcoming waste and pollution problems. The waste will be shredded into certain sizes and put into the cement kiln. The processing place is called a green zone. In this process, sometimes the material transport contains impurities in the form of metal and the like. This distribution has the potential to cause foreign material to be carried because there is no sorting of waste content. Belt conveyors and dynamic disc screens are often damaged by the metal material. This problem can be overcome with a magnetic separator to separate foreign metals from waste that is channeled using a belt conveyor. The magnetic separator provides protection for the dynamic disc screen and conveyor operating process from foreign material so that the potential for wear on the dynamic disc screen and torn belt conveyor can be avoided. The installation of the magnetic separator position uses a construction based on the optimal position. This study discusses the design and construction of the green zone belt conveyor magnetic separator installation. The construction installation for the magnetic separator aims to facilitate access to maintenance and cleaning, also provide access to dispose of foreign materials and protect the material transport system in the green zone. Before redesign magnetic sparator, the company spent Rp. 389,000,000 maintenance cost from November 2023 to February2024 period.  After redesign, it’s can reducing maintenance and repair costs during the period March 2024 to July 2024 with no maintenance related to metal separation.